Do Mutual Funds Attract the Right Investor? A Stochastic Dominance Approach - Seetharam, Yudhvir (Journal of Economics and Behavioral Studies, 2013)
Decision theory is concerned with identifying values and uncertainties in a given decision that result in the optimal outcome (Wald, 1939). It is one of the core aspects of any financial or investment decision. We consider the case where the investor has the choice between a passive index (such as a market index) and an actively managed mutual fund. Our analysis aims to determine which option an investor will choose based on a statistical ranking method known as stochastic dominance. We then evaluate this choice against the background information supplied by the mutual fund to ascertain whether the choice given by stochastic dominance is indeed in line with the investor profile given by the mutual fund. It is found that of the 11 mutual funds examined over the sample period of April 2006 to April 2013, only 4 attract the correct type of investor, 3 attract a mixture of investors and 4 attract (arguably) the wrong type of investor.